Using BPM to improve it service management: an incident management case study - Pereira, João Manuel Silva (2019)
Business process management is a methodology focused on the continuous improvement of business processes, providing for this a collection of best practices. These best practices enable the redesign of business processes to meet the desired performance. By using this methodology, organisations can improve their business processes to achieve their objectives. IT service management defines the management of IT operations as a service. There are several IT service management frameworks available, consisting in best practices that propose standardizing these processes for the respective operations. By adopting these frameworks, organisations can align IT with their business objectives. The objective of this research is to understand how business process management can be applied for the improvement of IT service management processes. To achieve this goal, a case study is conducted for the improvement of the time performance of an incident management process, as it is a process that, to the best of our knowledge, has not been analysed for this objective. The results obtained identified three best practices – activity automation, activity elimination and integral technology – as the best suited for the improvement of the time performance of the analysed incident management process. Using a simulation tool for business processes, it was revealed that the employment of these best practices in the analysed incident management process eliminates the effort required in the 1st support level and reduces in 10.7% the average processing time in the 2nd support level.